IMPROVING THE METHODOLOGY OF TEACHING SHORT-DISTANCE RUNNING TECHNIQUE IN PHYSICAL EDUCATION CLASSES WITHIN THE FRAMEWORK OF THE DEVELOPMENT STRATEGY (Web of Technology: Multidimensional Research Journal, 2026)
This article examines the improvement of the methodology for teaching short-distance running technique in physical education classes within the framework of the Development Strategy. The study focuses on the pedagogical conditions, methodological principles, and practical mechanisms that increase the effectiveness of sprint training among students. Particular attention is paid to the formation of correct running posture, start acceleration, stride coordination, finishing technique, and the gradual development of speed-strength qualities. The paper substantiates that the modernization of physical education lessons requires not only the renewal of content, but also the introduction of differentiated, competence-based, and student-centered teaching methods. In this regard, sprint training is considered as an important component of physical development, discipline, endurance, agility, and competitive readiness. The article also highlights the role of innovative pedagogical technologies, visual demonstration, repetitive drills, corrective exercises, and performance assessment criteria in the process of mastering sprint techniques. The findings show that improving the methodology of teaching short-distance running contributes to increasing students’ physical preparedness, motivation for sports, and interest in systematic physical activity. The proposed methodological approach may serve as an effective basis for optimizing physical education lessons in higher pedagogical education institutions.